Integrated management strategies for benign prostatic hyperplasia - Zhou, Yingchen; Luo, Qiao; Wang, Ruixiao; Zheng, Dongxiang; Xiong, Yaqing; Zuo, Jiao; Wang, Shusheng; Zhong, Liang (Frontiers in Urology, 2025)
Benign prostatic hyperplasia (BPH) is a common condition in aging men, leading to lower urinary tract symptoms (LUTS) that affect quality of life. Treatment options have evolved from invasive surgeries to a combination of pharmacological therapies, minimally invasive surgical therapies (MISTs), and standard surgical procedures. Medications such as α-blockers, 5-alpha reductase inhibitors (5-ARIs), and phosphodiesterase-5 inhibitors (PDE5i) are the first-line treatment for mild-to-moderate BPH, while MISTs like Rezūm, UroLift, Aquablation, and prostatic artery embolization (PAE) provide less invasive alternatives with shorter recovery times. For larger prostates, TURP and HoLEP remain the gold standards, offering effective long-term symptom relief despite some risks. Future advancements in BPH treatment focus on robotic-assisted surgery, AI-guided treatment selection, hybrid therapies, and regenerative medicine, aiming to enhance precision, reduce complications, and improve patient outcomes. This review summarizes current BPH management strategies and explores future innovations in the field.